1989
DOI: 10.1038/bjc.1989.56
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer, prostaglandins and patient survival

Abstract: Summary Prostaglandins may have both undesirable and desirable effects in malignant disease. Their possible roles in breast cancer were studied by examining the relationships between different variables and the amounts of prostaglandin-like material (PG-LM) extracted from 141 breast carcinomas. Univariate analysis indicates a direct correlation with patient age and menopausal status, with a greater yield from cancers of post-compared with pre-menopausal women. Tumours up to 2cm diameter yielded more PG-LM than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…To clarify the roles of the oxygenases in breast cancer, levels of their metabolites need to be defined and, similar to their parent enzymes, related to factors in the disease that alter survival. Radioimmunoassay studies conducted >20 years ago found that PG-like material in breast cancer was associated with an increase, no change, or a decrease in survival [29] and that PGE-like material was unrelated to tumor grade, estrogen receptors, node metastasis, or survival [30], [31], [32]. Perhaps because of these results and the need for fresh, specially processed tissues for study, newer measurement methods that unambiguously identify the metabolites of the COs and also the LOs in this disease are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…To clarify the roles of the oxygenases in breast cancer, levels of their metabolites need to be defined and, similar to their parent enzymes, related to factors in the disease that alter survival. Radioimmunoassay studies conducted >20 years ago found that PG-like material in breast cancer was associated with an increase, no change, or a decrease in survival [29] and that PGE-like material was unrelated to tumor grade, estrogen receptors, node metastasis, or survival [30], [31], [32]. Perhaps because of these results and the need for fresh, specially processed tissues for study, newer measurement methods that unambiguously identify the metabolites of the COs and also the LOs in this disease are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of prostaglandins in breast cancer was studied by Bennett and Rolland more than 20 years ago-they found raised prostaglandin levels in breast cancer tissue and indicated that prostaglandin production may serve as a prognostic marker. [6][7][8] Both COX-2 mRNA and protein levels were found to be raised in human breast cancer, 9 10 which was associated with decreased survival. 11 12 The application of NSAIDs was markedly associated with reduced development and progression of colonic tumours in patients with familial adenomatous polyposis (FAP), 13 14 whereas the data obtained on breast cancer are conflicting.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that PGs are important regulators of macrophages [16][17][18][19][20]. PGs produced by tumor cells or tumor-associated host cells (macrophages, endothelial cells, and stromal cells) have long been considered to play a stimulating role in the progression and metastasis of a variety of animal and human tumors [21][22][23][24]. The production and release of PGE 2 by tumors, in particular, have been associated with general suppression of immune responses.…”
Section: Introductionmentioning
confidence: 99%